Изготовление и эксплуатация оборудования из титана - Шеленков Г. М. Георгий Михайлович; Блащук В. Е. Виктор Евгеньевич; Мелехов Р. К. Ростислав Кузьмич; Романов О. Н. Олег Николаевич; Вовк С. Т. Степан Теодорович (Киев, Технiка, 1984)
Авт. указаны на обороте тит. л.